PENGEMBANGAN TES DIAGNOSTIK PADA MATERI HUKUM NEWTON DI SMA - Harfina, Lely; Maria Silitonga, Haratua Tiur; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to develop diagnostic test on Newton's law materials so that a test can be used to diagnose students misconceptions. The type of research conducted was research of development. The test was developed based on misconceptions which experienced by students on Newton's law material and was specially designed to detect students misconceptions. The results of the initial draft obtained 26 questions that had been validated by five lecturers and four teachers. The test was then tested in a small scale on 35 students of grade X in SMA Negeri 1 Pemangkat. Small-scale trial was conducted to determine the reliability and the level of difficulty of the questions. The results of the study on small-scale trial obtained the reliability value of 0.58. Furthermore, large-scale trials were conducted in SMA Negeri 1 Pemangkat, SMA Negeri 1 Semparuk, and SMA Negeri 1 Salatiga with the samples of 94 students. The results showed that there 15 questions of Newton's diagnostic test meet the diagnostic test criteria. It was indicated by the validator valuation of 0.82 for content validation, and reliability of 0.63, and readability level value of 5.67 which meant the test was easy to read by high school students.Keywords: diagnostics test, Misconception, Newton's Law